Solving taxonomic Orthoptera problems by Near Infrared Reflectance Spectroscopy (NIRS): the case of Aganacris Walker, 1871 (Tettigoniidae: Phaneropterinae; Scudderini) - Da Silva Sovano, Rafael S.; Gutjahr, Ana Lúcia Nunes; de Morais, José Wellington (Zootaxa, 2018)
Over the last 50 years, the genus Aganacris has undergone several taxonomic changes. In this study, an infrared spectrum analysis as a complementary and alternative analysis method was carried out for 112 Aganacris specimens belonging to five species. Significant differences were observed between males and females of the species, thus taking into account a new taxonomic status for the genus and the revalidation of Aganacris sphex (Rehn) stat. rev. The ability of Near Infrared Reflectance Spectroscopy (NIRS) to reproduce phenotypic (intra and interspecific) patterns in Aganacris populations was also verified. This method was applied, for the first time, as a taxonomic tool in the definition of individual sexual association and for the resolution of a taxonomic problem concerning Orthoptera, Tettigoniidae.